Factors Associated With Non-Adherence To Antidiabetic Medication Among Patients at Mbarara Regional Referral Hospital, Mbarara, Uganda - Faisal, Karekoona; Mekuriya, Tadele; Tusiimire, Jonans (Research square, 2021)
Background: Non–adherence is a major concern in treatment of diabetes mellitus and undermines the goals of treatment. The objective of this study was to determine the magnitude of non-adherence and its contributing factors among diabetes mellitus patients attending the Diabetes mellitus clinic at Mbarara Regional Referral Hospital. Objective: To assess the factors contributing to non-adherence to antidiabetic medication among diabetes mellitus patients in the Diabetic clinic at Mbarara Regional Referral Hospital Method: A descriptive cross-sectional study was done at the Diabetes clinic, Mbarara Regional Referral Hospital, between July and October 2020. Study participants were systemically sampled and data regarding their medication non-adherence was collected using a structured questionnaire, based on the Hill-Bone medication adherence scale. Data entry was done using Microsoft Excel Version 2010 and analysis was carried out using STATA version 13. Results: A total of 257 participants were recruited with 100% response rate. More than one third (98, 38.1%) of the participants were non-adherent to their antidiabetic medication. Age above 60 years (AOR = 6.26, 95%CI = 1.009–39.241, P = 0.049), and duration of diabetes mellitus above 5years (AOR = 1.87, 95%CI = 1.034– 3.392, P = 0.038) were independently associated with non-adherence to antidiabetic medication. Conclusion: The prevalence of non-adherence to antidiabetic medication was higher than that revealed in previous studies in Uganda. Patients with age above 60 years were six times more likely to be non-adherent to their antidiabetic medications. Patient education is important to address the challenge of medication non adherence.
Keywords: Non-adherence; Contributing factors; Prevalence; Antidiabetic drugs; Uganda